1982
DOI: 10.1111/j.1432-1033.1982.tb05823.x
|View full text |Cite
|
Sign up to set email alerts
|

Proline Biosynthesis in Escherichia coli. Purification and Characterisation of Glutamate-Semialdehyde Dehydrogenase

Abstract: Glutamate-semialdehyde dehydrogenase, catalysing the reduction in vivo of y-glutamyl phosphate to glutamate 5-semialdehyde in the pathway of proline biosynthesis in Escherichia coli, has been purified to homogeneity. High initial levels of the enzyme were achieved by using a multicopy ColEl-proA,B hybrid plasmid. The protein has a molecular weight of 1.89 x lo5 and consists of four identical subunits of molecular weight 4.7 x lo4 each. The pH optimum is 7.0 and the protein is stable for at least 10 min between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The induced protein of molecular weight 41.5k comigrated with purified GPR, and the induced protein of molecular weight of 37.0k comigrated with purified GK. The molecular weight of GPR is somewhat lower than that previously reported (18). Densitometric analysis of the Coomassie stained SDS-polyacrylamide gels indicated that GK and GPR together represented approximately 20-25% of the total soluble protein in the cell, with GPR accumulating in a 2 to 3-fold molar excess over GK (See Discussion).…”
Section: Nucleic Acids Researchmentioning
confidence: 64%
“…The induced protein of molecular weight 41.5k comigrated with purified GPR, and the induced protein of molecular weight of 37.0k comigrated with purified GK. The molecular weight of GPR is somewhat lower than that previously reported (18). Densitometric analysis of the Coomassie stained SDS-polyacrylamide gels indicated that GK and GPR together represented approximately 20-25% of the total soluble protein in the cell, with GPR accumulating in a 2 to 3-fold molar excess over GK (See Discussion).…”
Section: Nucleic Acids Researchmentioning
confidence: 64%
“…The gene is about 1300 bp for proA, which is what would be expected for a protein of the size seen. The protein is similar in size to the subunit molecular mass of 42000 Da seen for the E. coli enzyme (Hayzer & Leisinger, 1982) or 44000 Da for the Serratia enzyme (Omori et al, 1991). For leuB, the gene is 1400 bp, which could code for a protein of 51 000 Da, more than the 46000 Da observed.…”
Section: Identijication Of Gene Productsmentioning
confidence: 93%
“…The activities of y-glutamyl kinase and glutamate-y-semialdehyde dehydrogenase were assayed as described before (Hayzer ek Leisinger, 1982;Smith et al, 1984;Limauro et al, 1996). The hydroxamate assay was used to detect y-glutamyl kinase.…”
Section: Methodsmentioning
confidence: 99%